Vaccination strategies for solid organ transplant candidates and recipients: insights and recommendations - Christopher Radcliffe; Camille N. Kotton (Expert Review of Vaccines)
Introduction Vaccines save lives. They are integral to reducing the morbidity and mortality of vaccine-preventable infections in solid organ transplant recipients. Pre-transplant vaccination provides a unique opportunity for administration of live, viral vaccines, and enhanced vaccine efficacy, compared to the post-transplant period with decreased vaccine response due to immunosuppression.Areas covered We discuss a general approach to pre- and post-transplant vaccination in solid organ transplant candidates and recipients. We then review guideline statements and recent literature related to individual vaccines, including the recently developed respiratory syncytial virus vaccine. Travel and occupation-related vaccines are also discussed.Expert opinion The challenge of vaccination for immunocompromised patients expands as the prevalence of immunocompromised adults rises, and immunocompromised patients are frequently excluded from vaccine trials. In an age of vaccine hesitancy and reemerging vaccine-preventable infections, well-powered, prospective studies are needed to evaluate the clinical effectiveness of vaccines in solid organ transplant candidates and recipients.